A Critique of Legal Formalism in Handling Cyber Sexual Harassment: Efforts to Realize Substantive Justice Through a Gender Lens and Critical Education - Dian Paula April Juwan; Rr. Siti Murtiningsih; Sonjoruri Budiani Trisakti (UNISSULA, 2025)
Cybersexual harassment is a form of gender-based violence that is increasingly prevalent in the digital era, yet remains inadequately addressed in the Indonesian legal system. The dominant legal approach remains oriented toward formalism, with an emphasis on technical procedures and material evidence, often ignoring the suffering and vulnerability of victims, particularly women. As a result, victims not only struggle to access justice but also face additional trauma due to re-victimization during the legal process. This research uses a qualitative approach with normative-sociological methods to examine the limitations of legal formalism and the potential of a substantive justice approach in handling cybersexual harassment cases. Through an analysis of applicable regulations, literature reviews, and court decisions, this research integrates Paulo Freire's gender perspective and critical education as an interpretive framework. The results demonstrate that textually neutral laws are not necessarily just in practice, as they tend to ignore the social context and gender-based power inequalities. This research concludes that substantive justice can only be achieved through a reformulation of the legal paradigm that is responsive to victims' experiences and structural awareness. Critical education plays a strategic role in dismantling patriarchal bias in law and building gender-based legal literacy in society.